Advances in astrocytes in aneurysmal subarachnoid haemorrhage - Liu, Jiahui; Sun, Kun; Chen, Qiushi; Ding, Lianshu (Frontiers in Surgery, 2025)
Aneurysmal subarachnoid haemorrhage (aSAH) represents a subtype of stroke with a high incidence of morbidity and mortality. Astrocytes, the most abundant cell type in the central nervous system, play a pivotal role in brain injury and recovery following aSAH. They participate in synaptic remodelling, blood-brain barrier injury and the activation of the glial-mesenchymal-cervical lymphatic system. In this paper, we review the physiopathological functions and pathological changes of astrocytes after aSAH, exploring their mechanism of action in aSAH. We also summarise the evidence of therapeutic approaches to modulate astrocyte function after aSAH complications, and provide some new clues for future translational therapies to mitigate injury after aSAH.